DIGITAL CURRENCY IN INDIA: A CRITICAL REVIEW - Malik, Pooja; Anita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In today’s world , everything has been digitalised. The currency has also been digitalised. The RBI launched a pilot project for e rupee or digital rupee on 1 November, 2022. This is a pilot project which is conducted in 4 cities of India- Delhi, Mumbai, Bengaluru, Bhubaneshwar. Now the people have not required to take physical wallet in their pocket. In future , the physical currency will not be seen in the hands of general public. This is accepted as a legal tender. It includes the benefit of cryptocurrency and Fiat money. The physical wallet is replaced with digital wallet. Here, front end and back end transactions will be executed immediately. Many countries like China , Bahamas, Nigeria etc. have their own CBDC. This paper has been drafted to throw a light on the purpose behind the launch of digital currency by RBI , historical background and the issues and challenges of implementing e-rupee. This paper gives a glimpse of the current global scenario of central bank digital currency.